Effect of Time Management Training on Anxiety Depression and Sleep Quality - Ping WANG; Xiaochun WANG (Tehran University of Medical Sciences, 2018)
Background: Anxiety and depression seriously affect sleep quality and mental health of perimenopausal women. Time management training is of great value in relieving negative emotions and improving subjective well-being. This study aims to explore the effect of time management training on anxiety, depression, and sleep quality of perimenopausal women. Methods: From January 2018 to July 2018, 114 women with perimenopausal syndrome were randomly selected in Wuhan, Hubei Province of China as the objects of the experimental group (n=58) and the control group (n=56). The control group did not participate in any training in this study; time management training was conducted in the experimental group according to Getting Things Done, with a total of 12 training sessions over six months with two hours for each interval of two weeks. The effect of the intervention was evaluated before and after the experiment using relevant scales. Results: After the intervention, the Self-Rating Anxiety Scale (SAS) score and Self-Rating Depression Scale (SDS) score of the experimental group are lower than those of the control group (P<0.05). The Pittsburgh Sleep Quality Index (PSQI) score and Time Management Disposition Inventory (TMDI) score of the experimental group are higher than those of the control group (P<0.05). A positive correlation exists between the improvement in time management disposition and the improvement in anxiety, depression, and sleep quality (P<0.001). Conclusion: Time management training has a positive effect on improving anxiety, depression, sleep quality, and time management disposition of perimenopausal women.